PENERAPAN METODE AL-BAYAN TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN DI SMPN 2 GALESONG KABUPATEN TAKALAR - Ismail, Widia; Syahrul, Muhammad; Burhanuddin, Muh Azhar; Bunyamin, Andi; Nengsih, Ratika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the ability to read the Qur'an of class VIII B students of SMP Negeri 2 Galesong, Takalar Regency before and after the application of the Al-Bayan method, as well as to determine the improvement of students' ability to read the Qur'an through the application of the method. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, namely cycle I and cycle II. Each cycle consists of the planning stage, action implementation, observation, and reflection. The subjects of this study were 32 students of class VIII B of SMP Negeri 2 Galesong, Takalar Regency. Data collection techniques were carried out through observation, Al-Qur'an reading ability tests, interviews, and documentation. The aspects assessed in the ability to read the Qur'an include makhraj, tajwid, fluency, and tartil. The results of the study indicate that the ability to read the Qur'an of students before the application of the Al-Bayan method is still relatively low. After the application of the Al-Bayan method, the ability to read the Qur'an of students has increased in each cycle. This can be seen from the increase in the average value and percentage of student learning completion. In the pre-cycle stage, the average value of students was 78.41 with a completion percentage of 46.9% or 15 students reached the KKM. In cycle I, the average value increased to 83.07 with a completion percentage of 59.38% or 19 students reached the KKM. Furthermore, in cycle II the average value increased to 86.60 with a completion percentage reaching 100%, so that all students reached the specified KKM, which was 82. Thus, the Al-Bayan method is effective in improving the ability to read the Qur'an of class VIII B students of SMP Negeri 2 Galesong, Takalar Regency.